Improving Learning Outcomes of Students by Using Cooperative CIRC type (Cooperative Integrated Reading and Composition) Learning Model - Yanuar Tri Anggraini (Jurnal Axioma : Jurnal Matematika dan Pembelajaran, 2016)
The purpose of the research to describe the students activities during the learning process by using Cooperative Learning model in CIRC tipe  and describe increasing the students learning outcome during the learning process by using Cooperative Learning model in CIRC tipe. The kind of the research is PTK with qualitative and quantitative approach. The subjects of the research are students of class VIIIC at SMP Negeri 3 Bondowoso. With the data collecting method that used are documentation, observation, interview and test. The data analysis method that used is qualitative and quantitative. The results of the research there is increased activity and mathematic student learning outcomesKeywords: CIRC, students activity, and mathematical learning outcomes